Studies on Germination of Brown Rice Germ for the Development of High-Efficiency Automatic Germinating System - พวงสุวรรณ กฤษฎา - (Srinakharinwirot University Engineering Journal, 2019)
This research studies the germination behavior of brown rice for the development of automatic germination prototype for high efficiency. It can replace the culture of a community enterprise. This system consists of a heat and moisture content generator, water tray, brown rice tray and water tank. The automatic germination control systems included water filling, soaking, curing, leaching and controlling the temperature and relative humidity conditions. The germination of jasmine rice 105 was compared between the automatic germination and the community enterprise system in order to analyze the appropriate germination conditions and germ length at 24 and 48 hr. In addition, it also considers the economic dimension of the germination system. It was found that the germination time of 48 hours had optimum conditions for temperature control and relative humidity control at 35.25±0.66 °C and 53.29±2.40% RH, respectively. This has a significant effect on germination percentage and the germ length was 80±6.76% and 0.83±0.041 mm, respectively. They were higher than that of other germination. Moreover, the economic analysis of the germination system found that the germination capacity of brown rice was 540 kg per year. This system provided 16,956 Baht per year and 75,600 Baht per year of the electricity cost and the profit, respectively. Furthermore, the payback period was about 8 month and 15 days’ appropriate investments.